Building and Using Binoscopes - Butler, Norman (The Patrick Moore Practical Astronomy Series,, 2015)
Focusing on both homemade and commercial products, this book provides the reader with simple and straightforward information about the modelling and building of binoscopes. Binoscopes can be thought of as binoculars enlarged to the size of telescopes: essentially, a combination of the two. Constructing a binoscope is easier than most people think, but it still demands attention to detail and proper background knowledge. The author goes on to provide additional information about how to understand the products currently on the market, should the reader choose to purchase a binoscope instead of building one. Lastly, the book also compares binoscopes with telescopes in great detail, outlining the differences the reader can expect to see in the night sky from using both. The celestial views obtained with a binoscope, compared to a single telescope of the same aperture, are a very different experience and well worth the effort.